Analisis Pembelajaran Pendidikan Agama Islam Kurikulum 2013 Bagi Anak Berkebutuhan Khusus - Dinda Zulaikhah; Akhmad Sirojuddin; Andika Aprilianto (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2020)
This study aims to analyze the 2013 curriculum on educational materials especially for children with special needs. The method used in this research is literature study by analyzing the results of previous research and elaborating in content analysis. The result of this research is the need for a special curriculum for Islamic religious education material for special school children. It needs material simplification and a simple evaluation because not all special school children are able to evaluate according to general material. Teachers need patience in carrying out the learning process and also need to master various methods so that children don't get bored.